The Potential of Metabolism-Related Gene OGDHL as a Biomarker for Myocardial Remodeling in Dilated Cardiomyopathy - Tang, Yaohan; Zhu, Yaoxi; Lu, Yang; Yang, Hongmin; Yang, Han; Li, Lixia; Liu, Changhu; Du, Yimei; Yuan, Jing (Frontiers in Cardiovascular Medicine, 2022)
The development of dilated cardiomyopathy (DCM) is accompanied by a series of metabolic disorders, resulting in myocardial remodeling or exacerbation, while the mechanism remains not completely clear. This study was to find out the key metabolism-related genes involved in the onset of DCM, providing new insight into the pathogenesis of this disease. The datasets of GSE57338, GSE116250 and GSE5406 associated with hearts of DCM patients were downloaded from Gene Expression Omnibus database. GSE57338 was analyzed to screen out metabolism-related differentially expressed genes (DEGs), while GSE116250 and GSE5406 were utilized to verify the optimal genes through R software. Support Vector Machine Recursive Feature Elimination (SVM-RFE) algorithm and Least Absolute Shrinkage Operator (LASSO) algorithm were used to determine key genes. Finally, 6 of 39 metabolism-related DEGs were screened out and identified as the optimal genes. After qRT-PCR validation performed on the samples drawn from the left ventricles of human hearts, it showed that only the expression of OGDHL increased while PLA2G2 decreased significantly in DCM patients compared with nonfailing donors, respectively. Furthermore, the higher OGDHL protein expression except the change of PLA2G2 was also found in DCM hearts, and its mRNA expression was negatively correlated with myocardial masson scores (r=-0.84, p=0.009) and LVEDd (r=-0.82, p=0.014), which might be regulated by miR-3925-5p through the further bioinformatics prediction and qRT-PCR verification. The data then suggested that metabolism-related gene OGDHL was associated with myocardial fibrosis of DCM, and probably a biomarker for myocardial remodeling in DCM patients.